EFEKTIVITAS PENGGUNAAN MEDIA FLIP CHART BERBASIS BUDAYA LOKAL UNTUK MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SD N KRAPYAK WETAN - Yuniarti Dwirahayu; Beny Dwi Lukitoaji (STKIP Subang, 2025)
This study was conducted due to the low learning achievement of students in Pancasila Education. Based on Midterm Assessment (PTS) data, 60% of students did not meet the Learning Objective Achievement Criteria (KKTP). This situation highlights the importance of updating learning media to make it more interesting, enjoyable, and able to motivate students while learning. The purpose of this study was to determine the extent of the influence of local culture-based flip chart media on the learning achievement of Pancasila Education in fifth grade students at SD N Krapyak Wetan. This study used a quasi-experimental method, sometimes known as a pseudo-experiment. There were two groups of research subjects: the experimental class used local culture-based flip chart media, and the control class used video media. Data collection techniques included multiple-choice tests, observation, and documentation. The results of the study proved that the average post-test scores of students in the experimental class and the control class were significantly different. With an average score of 85.00 for the experimental class and an average score of 80.00 for the control class, there was a difference of 5.00 between the two. Based on the t-test results, HO was rejected and Ha was accepted because the post-test scores of the students who had been given the treatment had a significance value of 0.047, which is less than 0.05. Local culture-based flip chart media has been proven to be useful in improving student learning achievement.